2020
DOI: 10.3389/fpsyg.2020.559160
|View full text |Cite
|
Sign up to set email alerts
|

Supervisor Feedback and Innovative Work Behavior: The Mediating Roles of Trust in Supervisor and Affective Commitment

Abstract: This study aimed to explore how the mechanisms of supervisor feedback affect innovative work behavior (IWB) among local government employees and to examine the mediating roles of trust in supervisor and affective commitment, using organizational support theory (OST) and social exchange theory. The results from a cross-sectional study based on a sample of 1,699 local government employees from 65 local governments indicated that supervisor feedback had a direct effect on IWB. Trust in supervisor and affective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 85 publications
(140 reference statements)
2
40
0
1
Order By: Relevance
“…Therefore, the commitment of UFO Elektronika employees is very high so that they have high innovative thinking to participate in increasing the company's revenue (Marques et al, 2013). These results are in line with the research of Elshifa et al (2019), Ismail (2019, Tang et al (2019), Dahri (2018), Bak (2020), andAli et al (2020).…”
Section: The Effect Of Organizational Commitment On Innovative Work Behaviorsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the commitment of UFO Elektronika employees is very high so that they have high innovative thinking to participate in increasing the company's revenue (Marques et al, 2013). These results are in line with the research of Elshifa et al (2019), Ismail (2019, Tang et al (2019), Dahri (2018), Bak (2020), andAli et al (2020).…”
Section: The Effect Of Organizational Commitment On Innovative Work Behaviorsupporting
confidence: 91%
“…A series of innovation processes requires several employees who are committed to exchanging knowledge and creating a favorable atmosphere of innovation. Research conducted by Elshifa et al (2019), Ismail (2019), Tang et al (2019), Dahri (2018), Bak (2020), and Ali et al (2020) showed the results that the effect of organizational commitment on innovative work behavior was significantly positive. However, Serna et al (2018) stated that there was no effect on the relationship between organizational commitment and innovative work behavior.…”
Section: Introductionmentioning
confidence: 98%
“…First, we confirmed that the impact of leaders' positive feedback was identified as an important determinant factor for enhancing innovative behavior. Previous studies have mostly focused on the individual level performance, such as job satisfaction, and organizational commitment with a few exceptions [17,[23][24][25][26][27][29][30][31]. This study also confirmed the outcomes of previous literature by empirically demonstrating the positive influence of leaders' feedback on followers' innovative behavior in a Korean worker's context.…”
Section: Theoretical Contributionssupporting
confidence: 85%
“…Previous studies regarding leaders' feedback have often investigated its relation with business performance, job satisfaction, and organizational commitment [17,[22][23][24][25][26][27]. For example, Zhou [28] found that leader feedback positively related to members' personal creativity, but, with a few exceptions, there were limitations in showing the relationship to individual innovative behavior and the change process behind such behaviors [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation